The significance of freedom in God"s plan - May, Andreas (HTS teologiese studies, 2023)
By means of a synthesis of Christian faith, theology and natural sciences, the significance of freedom in God’s plan of creation and redemption was contemplated. The triune God is the foundation of all freedom. The freedom of his creatures is extremely important to God. Despite the Angelic Fall, he created our universe, in which on the path of evolution human beings were given the freedom to choose for or against God. Possibly, the humans who committed the Adamic Fall belonged to the species Homo heidelbergensis. Through the perfect obedience of Jesus Christ to the point of death on the cross, the power of evil was overcome. The goal of all creation is ‘the freedom of the glory of the children of God’ (Rm 8:21). This will complete the freedom that God has placed in his creation from the beginning. It can be surmised that ‘the freedom of the glory of the children of God’ includes being integrated into the intra-Trinitarian communion. It is important for the fulfilment of God’s plan of redemption that more and more people follow Jesus Christ and try to become more and more like him. A crucial point in following Christ is obedience. Obedience and freedom are not a contradiction, but the two sides of a coin; and the metal of this coin is love.Contribution: The synthesis of Christian faith, theology and natural sciences made it possible to see more clearly how extraordinarily important human freedom is for God. This is not only important for theological research, but also has practical consequences for human beings.